STUDI KASUS MENGGURANGI TINDAKAN BULLYING DENGAN MENGGUNAKAN MEDIA FILM PADA ANAK DI PANTI ASUHAN YATIM PUTRI AISYIYAH II SURAKARTA TAHUN 2021 - Afifah, Resiana Nur (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
The purposesIofIthisIstudyIwere 1) toIanalyze the bullying in the Putri Aisyiyah II orphanage in Surakarta, 2) to find out about the impact experienced by both victims and bullies when bullyingIoccurred, 3) to find out the impact of reducing bullying by using given film media. TheIresearchImethodIused is a descriptiveIqualitative research. TheIresearch subjects were 1 child who was a bully, aIvictimIofIbullying, a friend of a victim of bullying, a friend of a bully and a foster parent in an orphanage. Data collection techniquesIareIthroughIinterviews,Iobservation,IandIdocumentation. TheIdata analysisItechnique used method triangulationIand timeItriangulation. The research data were analyzed using cycle models such as dataIreduction, dataIdisplay, drawing conclusions orIverification. BasedIonItheIresultsIof theIstudy, itIcould beIconcluded that 1) there was one child in the Putri Aisyiyah II orphanage in Surakarta who did bullying, 2) bullying was overcome by the way the child got services about behavior change. In addition, the child also got an approach from foster parents and was given certain sanctions, 3) the provision of film media for children was also able to make children reduce their bullying actions. This was due to the moral message in the film that was shown so that children could easily understand the impact that occur when children were bullying their friends at the orphanage, 3) the factors that caused children to do bullying were because children felt the strongest of their friends, were selfish, and could not accept the condition of friends and the child had been bullied before.